Pengenalan Cagar Geologi Dalam Upaya Pelestariannya Sebagai Salah Satu Aspek Geoheritage Daerah Mangilu Kabupaten Pangkep - Haerany Sirajuddin; Hendra Pachri; Adi Tonggiroh; Rohaya Langkoke; Adi Maulana; Musri Mawaleda; Safri Burhanuddin; Hamid Umar; Ilham Alimu ddin; Yanny .; Savira Aulia; Hardiani Rantetondok (Faculty of Engineering UNHAS, 2026)
This community service activity aims to inventory aspects of the Mangilu geological reserve through field observations, as well as increase public awareness of the concept of geological reserves, the importance of geoheritage, and sustainable participatory preservation strategies, as well as foster a sense of pride and ownership in the community towards their local geological wealth. The implementation method includes field observations to obtain initial data on the geological reserve to be socialized. The socialization process uses an interactive presentation method that explains the area's geological potential, its benefits to the community, and sustainable conservation measures. The inventory results show that the Mangilu area has extraordinary geological diversity with unique characteristics with very diverse rock components from various origins and formation periods, including outcrops of autoclastic breccia and altered kaolin from the Mallawa Sandstone, several outcrops of autoclastic breccia containing serpentinite blocks, broken and deformed chert, marble blocks and pillow lava, Tonasa limestone with boudin (pinch and swell) structure and basalt dikes intruding hyaloclastic rocks. This is clear evidence of the intensive tectonic processes of the Bantimala Complex. This geological diversity makes Mangilu have high potential to be developed as a geological reserve and geoheritage that is valuable as a source of knowledge for further geological research, a valuable learning object, and an educational tool. The socialization activity in the form of an interactive presentation delivered successfully increased public understanding and awareness of the concept of geological reserves, where before the socialization was carried out, 15% showed very understanding, 19% understood, 35% did not understand, and 31% did not understand. After the socialization activity, there was an increase in understanding to very understanding 49%, understanding 28%, not understanding 18% and not understanding 5%. Keywords: Geological Reserve; Mangilu Area; Conservation; Geoheritage